(3cJGH aj GdWH ` GdGOhjI GdeaQOIs - (3YeQ Hf Ydj Hf ZjdGf GdHdNj, GaVd GdOjfs
(3ChdgG (B:s
(3bGd GdTjN Efi JUaMJ cJGH GdGOhjI GdeaQOI ef cJGH GdbGfhf ai GdWH dGHi Ydi Hf SjfG s
(3BNQgG (B:s
(3ai cJGH Ufag ai EKHGJ MOhK GdYGde adPdc cGf gPG GdfeW ef GdcdGe hCf GdNWC Ydjg eMGd Je HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSI hGdYTQhfs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs